Instrumental Assessment of Pulmonary Function in Late Post-COVID-19: An Integrative Review (CIPEEX, 2026)
Introduction: Following the significant impacts of the pandemic caused by the SARS-CoV-2 virus, it is of utmost importance to determine the most effective approach for evaluating pulmonary function in patients who have faced the disease, as well as to identify the most commonly used instruments for this purpose. Objective: To analyze the devices used in the evaluation of pulmonary function in patients in the late post-Covid-19 period. Method: This is an integrative review of the scientific literature on this topic. For data collection, the following databases were used: Virtual Health Library (VHL), PubMed Unique Identifier (PubMed), Latin American and Caribbean Health Sciences Literature (LILACS), and Scientific Electronic Library Online (SciELO). Articles in English, Portuguese, and Spanish, published within the last 5 years, were selected. Results: 22 articles were analyzed, which revealed that the use of spirometry in 22 studies proved essential for identifying ventilatory patterns, although in many cases, the mean values of FVC and FEV1 were within the normal range. Pulmonary diffusion capacity (DLCO), evaluated in 12 articles, was consistently the most common and persistent marker of dysfunction. Other instruments, such as the Six-Minute Walk Test (6MWT), manovacuometry to assess respiratory muscle strength, and impulse oscillometry (IOS), were also used to diagnose functional limitation and small airway dysfunction, respectively. Conclusion: The most commonly used instruments to evaluate pulmonary function are spirometry, DLCO, Manovacuometry, IOS, and the 6MWT.
Keywords: Covid-19; espirometria; avaliação respiratória; testes respiratórios